Exchange Rate Risk : Reviewing the Record for Private Infrastructure Contracts - Gray, Philip; Irwin, Timothy (World Bank, Washington, DC, 2012)
Among the key risks facing foreign private entities investing in the infrastructure of developing countries is depreciation or devaluation of the local currency. Indeed, over the past 25 years developing country currencies lost 72 percent of their value relative to the U.S. dollar on average-and about a fifth lost more than 99 percent of their value. Sustainable private investment in infrastructure depends on addressing this risk well. Private infrastructure contracts in developing countries have usually passed much of this risk on to customers or the government. But because devaluations and large depreciations in developing countries often occur in the context of macroeconomic and financial upheaval, such risk allocations cannot always be made to work. The difficulty arises because the contracts raise prices precisely when the economy is suffering the most. If the government bears the risk because a state-owned utility is purchasing power from an independent power producer at prices denominated in U.S. dollars, for example, a contract will require steep increases in local currency prices just when the utility ' s revenues-and those of its owner, the government-are likely to be declining.